Resource efficient injection moulding with low environmental impacts - Gantar, Gašper (Strojniški vestnik, 2013)
The selection of most appropriate design and technological solutions to produce certain mould should capture technical performance, economical issues as well as environmental impacts occurred during the mould life cycle. In the paper an approach is presented to support the selection of alternative mould design solutions in the early design stage. It includes the use of Life Cycle Assessment methodology, Life Cycle Cost methodology and is supported by numerical simulations. The approach is applied to a case study where three mould designs for production of the same plastic product were compared. Finally, general conclusions regarding the resource efficient injection moulding processes are presented.
Keywords: analiza stroškov; analiza življenjskega cikla; brizganje plastike; cost analysis; injection moulding; life cycle assessment; mould; optimisation; optimizacija; orodje